Organizing space and time through relational human-animal boundary work: exclusion, invitation and disturbance - Dan Sage; Lise Justesen; Andrew Dainty; K. Trygesstad; Jan Mouritsen (2016)
In this paper we examine the role that animals play within human organizational boundary work. In so doing, we challenge the latent anthropocentricism in many, if not most, theories of organization that locate animal agencies outside the boundary work that is said to constitute organizing. In developing this argument we draw together diverse strands of work mobilizing Actor-Network Theory that engage the entanglement of human/nonhuman agencies. In bringing this work together we suggest humans may organize, even manage, by conducting relational boundary work with animal agencies, spacings and timings. Our argument is empirically illustrated and theoretically developed across two cases of the spacings and timings of construction project organizations – an infrastructure project in the UK and a housing development in Scandinavia. Construction projects are well-known for their tightly managed linear timings and for producing the built spaces that separate humans and animals. Three concepts – Invitation, Exclusion and Disturbance – are offered to help apprehend how such organizings of space and time are themselves dependent upon entanglements between human and animal agencies. We conclude by suggesting that animals should not be negatively constituted as an ‘Other’ to human organizing, or indeed management, but rather acknowledged as sometimes constituting human capacities to organize, even managerially control, space and time.